Shifting identities: The musician as theatrical performer - Hübner, Falk (Utrecht HKU research centre, 2014)
The artistic PhD research "Shifting Identities" investigates the musicians' professional identity and how this identity might shift when musicians start acting as theatrical performers. In most of the theatrical situations where musicians "perform", their profession is extended by additional tasks such as walking on stage or reciting text. As an alternative strategy to extension, this research introduces and focuses on reduction, which means the abstracting away of specific qualities or abilities of the musician's profession. The audience watches musicians not doing certain things that usually belong to their profession. Both the expansive and the reductive approaches are concepts of working theatrically with musicians. They are different, perhaps even contradictory strategies, but both bear the ability to enrich the musician's professional identity with a more theatrical appearance. In order to build an understanding of what is extended or reduced when the identity shifts from a musician to a theatrical (musician-)performer a dynamic model is developed which builds strongly on what musicians actually do, a model that categorises the musician's professional activities into internal, external and contextual elements.